Eco-Friendly Synthesis of 1H-benzo[d]imidazole Derivatives by ZnO NPs Characterization, DFT Studies, Antioxidant and Insilico Studies - Samar M. Mohammed; Wesam S. Shehab; Abdul-Hamid M. Emwas; Mariusz Jaremko; Magda H. Abdellattif; Wael A. Zordok; Eman S. Tantawy (MDPI AG, 2023)
Benzimidazoles are classified as a category of heterocyclic compounds. Molecules having benzimidazole motifs show promising utility in organic and scientific studies. A series of mono-substituted benzimidazoles were synthesized by ZnO-NPs via cyclocondensation between substituted aromatic aldehydes and o-phenylene diamine. The synthesized compounds were characterized and compared with the traditional methods. The nano-catalyzed method displayed a higher yield, shorter time and recyclable catalyst. The DFT study and antioxidant activity were investigated for benzo[d]imidazole derivatives. Compound 2a exhibited the highest antioxidant activity among the tested compounds. We focused on the catalytic activity of ZnO in the synthesis of heterocyclic structures with the goal of stimulating further progress in this field. The superiorities of this procedure are high yield of product, low amounts of catalyst and short reaction time.